2008
DOI: 10.1002/ptr.2596
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Achillea millefolium essential oil in diploid cells of Aspergillus nidulans

Abstract: The essential oil of Achillea millefolium is commonly used in folk medicine for the treatment of several diseases and has been demonstrated previously to exert an in vitro antimicrobial activity against human pathogens. Current study investigates the genotoxic activity of A. millefolium oil. The oil's major constituents are: chamazulene (42.15%), sabinene (19.72%), terpin-4-ol (5.22%), beta-caryophyllene (4.44%) and eucalyptol (3.10%), comprising 74.63% of the total. The oil's genotoxic evaluation was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…This EO exerted genotoxic effects against the fungal cells and suppressed the development of spores. [208] As the study mentioned below shows, the fungistatic activity of EOs can be influenced by the existing pH level. Penicillium verrucosum, Penicillium expansum and A. ochraceus were more sensitive to Ocimum gratissimum L. (Lamiaceae) EO compared to the EOs of Thymus vulgaris L. (Lamiaceae) and C. citratus.…”
Section: Juniperus Phoenicea L (Cupressaceae)mentioning
confidence: 98%
“…This EO exerted genotoxic effects against the fungal cells and suppressed the development of spores. [208] As the study mentioned below shows, the fungistatic activity of EOs can be influenced by the existing pH level. Penicillium verrucosum, Penicillium expansum and A. ochraceus were more sensitive to Ocimum gratissimum L. (Lamiaceae) EO compared to the EOs of Thymus vulgaris L. (Lamiaceae) and C. citratus.…”
Section: Juniperus Phoenicea L (Cupressaceae)mentioning
confidence: 98%
“…Achillea millefolium L. (Asteraceae), commonly known as yarrow, is an ancient remedial herb native to Europe and is used to treat wounds, gastrointestinal and hepatobiliary disorders, hemorrhages, spasmodic diseases, inflammation, headaches, and pain [5, 6]. Phytochemical screenings revealed that chemical constituents of A. millefolium (AM) present several secondary metabolites, including essential oils, sesquiterpenes, the alkaloid achilleine, steroids, triterpenes, and flavonoids, as presented by De Souza et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Monografias no assunto encontram-se postadas na Farmacopéia Portuguesa (Cunha & Roque, 2009) e na British Herbal Pharmacopoeia (1996). Investigações fitoquímicas de extratos alcoólicos levaram ao isolamento de pequenos metabólitos, como lactonas, sesquiterpenos e flavonóides (Sant'Anna et al, 2009), sugerindo o controle de fitopatógenos pelos componentes do óleo essencial de mil folhas. Schwan-Estrada et al (2000) quantificaram a produção das fitoalexinas deoxiantocianidinas em mesocótilos de sorgo, e de gliceolinas em cotilédones de soja, após tratamento com extratos de quinze plantas medicinais (incluindose mil folhas), e apontaram o potencial uso desses extratos no controle de fitopatógenos e na indução de resistência das plantas contra doenças.…”
Section: Introductionunclassified